Saving a Life: Suicide Prevention - Rezvan SadrMohammadi; Somayeh Hadad Ranjbar; Reza Bidaki (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2024)
Introduction: Suicide is considered as a serious and important problem in health and comprehensive health. Every year, approximately 700,000 people around the world die by suicide, which is more than those killed in war. Death by suicide is not only the loss of a life, but it also causes psychological damage to the other family members and friends. Important factors affect suicidal behavior. So much suicide is a serious public health problem. All 194 member states of the World Health Organization have signed the Comprehensive Mental Health action plan 2013-2020, which tasks governments with implementing evidence-based interventions in community settings to prevent suicide at all stages of life. In addition, the guardians of mental health also play an important role in the prevention of suicidal behavior.